Physiological differences of five Holm oak (Quercus ilex L.) ecotypes growing under common growth conditions were related to native local climate. Issue 3 (11th August 2015) - Varone, Laura; Vitale, Marcello; Catoni, Rosangela; Gratani, Loretta
Abstract: An increase in the frequency and intensity of extreme climatic conditions is expected for the Mediterranean area as a response to climate change. As a consequence, the ability of Mediterranean plant species to adapt to complex and stressful environmental conditions plays an important role in driving their future distribution. The adaption of plant species may be expressed by ecotypes already adapted to local climate. Our goal was to analyse the seasonal physiological behaviour of five Q uercus ilex ecotypes coming from different Italian geographical areas (from the north to the south) in order to test if ecotypes maintained their physiological traits when grown in the same environmental conditions. Measurements of gas exchange, biochemistry and chlorophyll fluorescence carried out during winter, spring and summer underlined that the response of the considered ecotypes reflected the climate of the original provenances, particularly under suboptimal conditions. The ecotypes from the northernmost and the southernmost limits were the most sensitive to high and low temperatures, respectively. Our results can be used to advance hypotheses about the respone of Q . ilex to climate change. Abstract : The adaptive responses of the species to changes in environmental factors may depend on their intra‐specific differences. The considered ecotypes, grown under the same climatic conditions, exhibit a significant variation in physiological traits. The study reveals the existence of a geographic variation pattern at a functional level since these differences are in relation to different ecotypes native sites.